Campesinos de pie: La formación del movimiento campesino en Formosa - Vázquez, Cristian (Entre los libros de la buena memoria, 2020)
In 1971 the Unión de Ligas Campesinas Formoseñas (ULICAF) emerged. This research reviews the political, economic and ecclesiastical transformations that gave rise to its emergence.